Pengaruh Metakognitif Terhadap Hasil Belajar IPS di Sekolah Menengah Pertama (SMP) Negeri Kabupaten Banyuwangi - Ismaul Fitroh; Moh. Imron Rosidi (Journal on Education, 2023)
This research aims to determine how much influence metacognitive has on student learning outcomes in junior high school social studies subjects in Banyuwangi Regency. This research uses a quantitative research method which includes observation, interviewing teachers and students, and distributing questionnaires to students. The results showed that a thitung of 24,042 was obtained. At degrees of freedom (df) = n – 2 = 90 – 2 = 88, then the ttabel values at the 95% confidence level are -1.987 and 1.987. Because thitung > ttabel , then H0 is rejected and H1 is accepted. Thus, it can be concluded that at the 95% level of confidence, metacognitive variables have a significant effect on student learning outcomes.